2009
DOI: 10.1075/wll.11.2.03tre
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phonological awareness training on reading achievement

Abstract: Phonological awareness is usually considered to be an important prerequisite for success in literacy acquisition. Children who had phonological awareness training in preschool not only show a better performance in phonological awareness tasks at elementary school but also perform better in reading and writing than untrained children. As part of the EVES longitudinal study, reading and spelling skills of 1520 children who entered school in the fall of 2001 and 2002 were assessed throughout elementary school. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 0 publications
0
0
0
1
Order By: Relevance
“…Much of the research on spelling has focused on either documenting the development of spelling ability in children gaining L1 literacy or assessing the effectiveness of instructional techniques for improving L1 spelling (and other literacy skills). For example, studies have consistently found that phonics-based instruction is effective for improving spelling skills as well as reading ability, and that these effects can persist for years [8,[40][41][42]. However, the vast majority of this research has focused specifically on children learning to spell in their L1, most commonly English.…”
Section: Spelling Developmentmentioning
confidence: 99%
“…Much of the research on spelling has focused on either documenting the development of spelling ability in children gaining L1 literacy or assessing the effectiveness of instructional techniques for improving L1 spelling (and other literacy skills). For example, studies have consistently found that phonics-based instruction is effective for improving spelling skills as well as reading ability, and that these effects can persist for years [8,[40][41][42]. However, the vast majority of this research has focused specifically on children learning to spell in their L1, most commonly English.…”
Section: Spelling Developmentmentioning
confidence: 99%
“…Τις τελευταίες δεκαετίες, η αδιάλειπτη ανάδειξη του εξέχοντα ρόλου των πρώιμων δεξιοτήτων μεταφωνολογικής επίγνωσης στην πρόσκτηση των δεξιοτήτων συμβατικού γραμματισμού (Ball & Blachman, 1991, Blachman, Ball, Black, & Tangel, 1994, Bradley & Bryant, 1983, Bryant, Bradley, MacLean, & Crossland, 1989, Byrne & Fielding-Barnsley, 1991, Castle, Riach, & Nicholson, 1994, Catts, Fey, Zhang, & Tomblin, 1999, Cossu, Shankweiler, Liberman, Katz, & Tola, 1988, Cunningham, 1990, Durgunοğlu, Nagy, & Hancin-Bhatt, 1993, Durgunοğlu & Öney, 1999, Fox & Routh, 1984, Gottardo, Stanovich, & Siegel, 1996, Iversen & Tunmer, 1993, Juel, Griffith, & Gough, 1986, Leather & Henry, 1994, Liberman, Shankweiler, Fisher, & Carter, 1974, Lundberg, Frost, & Peterson, 1988, Manrique & Signorini, 1994, Muter, Hulme, Snowling, & Taylor, 1997β, O'Connor, Notari-Syverson, & Vadasy, 1996, Perfetti, Beck, Bell, & Hudges, 1987, Schneider, Küspert, Roth, & Visé, 1997, Share, Jorm, MacLean, & Matthews, 1984, Stanovich, Cunningham, & Cramer, 1984, Storch & Whitehurst, 2002, Tornéus, 1984, Treiman & Baron, 1983, Treutlein, Zöller, Roos, & Schöler, 2008, Vellutino & Scanlon, 1987, Wimmer, Landerl, Linortner, & Hummer, 1991 είχε ως αποτέλεσμα την ανάπτυξη και στάθμιση εργαλείων μέτρησης που επικεντρώνονται στην αξιολόγηση των μεταφωνολογικών δεξιοτήτων των παιδιών προσχολικής και πρώτης σχολικής ηλικίας (H...…”
Section: οριοθέτηση του προβλήματοςunclassified